الملح والنكت واللطائف في التفسير - ابن القيم أنموذجا - - مزغيش, صليحة (University of Eloued جامعة الوادي, 2018)
"هذه الدراسة بعنوان: الملح والنكت واللطائف في التفسير -ابن القيم أنموذجا-, وهي تعالج الإشكالية: كيف أظهر الإمام ابن القيم بلاغة وأسرار الألفاظ في القرآن؟ حيث قسمتها إلى مقدمة؛ احتوت على أهمية الموضوع وأهدافه وأسباب اختياري له والإشكالية والمنهج المتبع فيه كذا الدراسات السابقة, وأجبت عن الإشكالية السابقة وغيرها من خلال ثلاث مباحث, حيث خصصت مبحثا تمهيديا عرفت فيه المصطلحات المتعلقة بالبحث لغة واصطلاحا, كما ذكرت مواردها في كتب التفسير, وكذا فوائدها, ثم المبحث الأول الذي تطرقت فيه إلى ترجمة الإمام ابن القيم ترجمة موجزة, ثم ذكرت منهجه في التفسير ومصادره ومؤلفاته فيه, وفي الجانب التطبيقي لهذه الدراسة قمت بانتقاء مجموعة من الأمثلة عن اللطائف من كتب ابن القيم في التفسير وصنفتها إلى الكلمة وتراكيب الجملة, الذي وردت فيها اللطيفة, وقد ختمت هذه الدراسة بخاتمة سردت فيها أهم النتائج التي توصلت إليها مرفقة بأهم التوصيات, ولعلَّ أهم النتائج التي توصلت إليها من هذه الدراسة: 1- أنه كان لابن القيم حسٌ بلاغيٌ وبيانيٌ, لطيفٌ بارعٌ شيقٌ في تناول ألفاظ القرآن الكريم. 2-أن الإمام ابن القيم كانت له طريقة خاصة في تفسير الآيات, حيث يتناول الألفاظ ويستخرج منها اللطائف البيانية والأسرار البلاغية. " "Study Summary This study is entitled: Molah, Jokes and Lataif in the interpretation of Ibn al-Qayyim as a model. It deals with the problem: What is the method of Imam Ibn al-Qayyim in highlighting the meanings and precise indications of the Holy Quran ? which divided it into an introduction; it included the importance of the subject and its objectives and reasons. In the same way as previous studies, and I answered the previous problem and others through three studies where I devoted a preliminary study in which the terminology related to research was known as language and terminology, as I mentioned in the books of interpretation and its benefits.Then I mentioned his method of interpretation, its sources its writings. In the practical aspect of this study, I have selected a number of examples of al-Taif from Ibn al-Qayyim's books on interpretation and classified them into the word and structure. The sentence, which was nice, ended with a conclusion that listed the most important findings Accompanied by the most important recommendations recommendations, and perhaps the most important findings of this study: 1 - that Ibn al-Qayyim had a sense of communication and a pleasant and interesting text in dealing with the words of the Holy Quran. 2 - that Imam Ibn al-Qayyim had a special way of interpreting the verses, where he deals with the words and extract from them the graphic and rhetorical secrets. "
مذكرة ماستر تخصص تفسير وعلوم القرآن
Keywords: الملح ،النكت، اللطائف; ELMOLAH, The jokes, ELLATAIF